Diagnosis of civil Construction Waste Management from the reading of the urban landscape - Quaglio, Renan Serraglio; Arana , Alba Regina Azevedo (Sociedade & Natureza, 2020)
Civil construction can be identified as one of the sectors that most cause impacts to the environment due to exploitation of natural resources and high rate of waste generation. In this context, this study aims to list the main areas of inappropriate disposal of RCD in the municipality of Presidente Bernardes-SP presenting its characteristics and spatial analysis. The methodological procedures for the characterization of the areas were constituted by visits to the disposal points, photographic registration geographical coordinates demarcation and direct observation of the RCD composition. After a detailed investigation of the urban perimeter and accesses of the municipality were demarcated 40 points of irregular disposal that had more than 3 m³ of deposited RCDs. The area of the municipality was subdivided according to the urban features. Class A, 82.5% of Class B, 47.5% of Class C and D were identified in all the analyzed points, it was also verified that 20% of the points had household residues evidencing the power attractiveness of RCDs. From the results it was possible to relate the main areas of irregular disposal, as well as to estimate the volume of waste discarded and its composition, providing subsidies to the implementation of a differentiated management in the municipality.